2021
DOI: 10.19128/turje.832203
|View full text |Cite
|
Sign up to set email alerts
|

Öz-Belirleme Kuramı perspektifinden sınıf öğretmenlerinin motivasyonu ve motivasyon etkenleri

Abstract: This study examines the motivation of primary school teachers from the perspective of selfdetermination theory, to identify the variables and factors that affect motivation. The research was conducted using an explanatory mixed design. The qualitative data were collected from 414 teachers from 39 schools covering all districts of Erzurum province through the Multidimensional Job Motivation Scale. Qualitative data were collected from 30 participants through the Teacher Interview Form. Quantitative data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
2
0
2
Order By: Relevance
“…En ese sentido, el teletrabajo se convierte en un vehículo que canaliza esas necesidades a través de la motivación intrínseca (Rigby & Ryan, 2018;Ryan & Deci, 2020). Posiblemente, los beneficios asociados al teletrabajo transmiten el suficiente interés y seguridad personal para que la motivación intrínseca se comunique con el comportamiento creativo mediante la mejora de la persistencia, el desempeño, la autoestima y la autopercepción de bienestar (Yildiz & Kiliç, 2021).…”
Section: Discusión De Resultadosunclassified
See 1 more Smart Citation
“…En ese sentido, el teletrabajo se convierte en un vehículo que canaliza esas necesidades a través de la motivación intrínseca (Rigby & Ryan, 2018;Ryan & Deci, 2020). Posiblemente, los beneficios asociados al teletrabajo transmiten el suficiente interés y seguridad personal para que la motivación intrínseca se comunique con el comportamiento creativo mediante la mejora de la persistencia, el desempeño, la autoestima y la autopercepción de bienestar (Yildiz & Kiliç, 2021).…”
Section: Discusión De Resultadosunclassified
“…Así mismo, esa probable motivación sostenida durante todo el período de trabajo virtual hará que el empleado tenga mayor interés, pasión, persistencia y seguridad personal para desempeñarse creativamente (Yildiz & Kiliç, 2021). En realidad, la motivación conduce al ser humano a buscar cambios, retos difíciles, y a explotar las propias capacidades de aprendizaje.…”
Section: Introductionunclassified
“…In the field of human interpersonal behaviour, this idea is based on two criteria: the first is related to the need for frequency in affective interactions, and the second is that interactions take place in a stable context and seek the well-being of the individual (Baumeister & Leary, 1995;White et al, 2021). An important aspect is that the satisfaction generated from interacting with other individuals could increase or decrease over time (Yildiz & Kiliç, 2021). In this way, it is confirmed that the attitude towards behaviour, subjective norms, and perceived behavioural control are influenced by the emotions resulting from interactions with others, especially regarding healthy eating behaviour (Baumeister & Leary, 1995;Jones et al, 2021).…”
Section: The Need For Relatedness As An Individual Needs From Self-de...mentioning
confidence: 99%
“…By achieving success in one's career and experiencing a sense of personal fulfillment, we might say that we are experiencing "intrinsic contentment." Career opportunity, category of skills, application of skills, task significance, and feedback are the five pillars of Maslow's (1954) hierarchy of needs, which can be satisfied (Yildiz & Kiliç, 2021) When researchers talk about an employee's level of satisfaction with their jobs as a whole, we're referring to the aggregation variables that make up that score. The job satisfaction is significant predictor of employees' happiness at workplace.…”
Section: Literature Reviewmentioning
confidence: 99%